Economical rations for beef production with feeds adapted to western Kansas - Evans, William K (My University, 1905)
Introduction:The last fifteen years in Western Kansas has been a period of great change, and the stockmen and feeders have been confronted with the question of economical beef production. This has been due to the increase in population in the East, and the steady flow of immigration from the Eastern countries, moving the center of population of the United States westward, with the result that in the last ten or fifteen years the plains of Kansas have been rapidly settled up. This has been a benefit to Kansas as a state no doubt, but to the cattleman, who before this increase in population, had had unlimited range for their cattle, the result has been financial disaster to the cattle business as formerly carried on, on account of the introduction of crops. In the early days before this period of settlement began the cattlemen had unlimited range for their herds which grazed and fattened all year on the rich, palatable and nutritious buffalo grass which covered the plains, and possessing the desirable quality of curing on the ground, made, owing to the mild winters, a method of beef production that never has, nor probably never will be equaled. The buffalo grass had great fattening properties and the cattle being allowed to run until they had reached an age of four to five years were sold at a good price, and as their cost was nothing the profits were enormous, and the cattlemen grew rich. These conditions, however, could not continue always. The farmer was steadily pushing westward along the streams and taking up homesteads wherever a suitable location was found; steadily cutting down the cattleman's range and forcing him to build fences to keep his stock away from crops.
Citation: Evans, William K. Economical rations for beef production with feeds adapted to western Kansas. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Buffalo Grass; Kaffir Corn; Indian Corn; Theses